PEMETAAN WILAYAH POTENSIAL PENGEMBANGAN PETERNAKAN BABI DI KABUPATEN MANGGARAI MENGGUNAKAN APLIKASI QGIS - N. S., DALLE; CALING, C. L. B.; TUKAN, H. D.; NUGRAHA, E. Y. (Majalah Ilmiah Peternakan, 2024)
This study aims to map potential areas for pig farming development in the Manggarai Regency area. The method used in this study is secondary data observation in 12 Kecmatan in Manggarai Regency and will be analyzed using Location Quotient (LQ) analysis. The data that has been analyzed is then mapped using the Quantum GIS appli- cation to see areas that have the potential to develop pig farms in the Manggarai Regency area. The results of this study are the sub-districts of Satar Mese, Satar Mese Barat, Wae Ri’i, Cibal and Reok Barat get LQ<1 results which means that the region has not been able to meet the needs of its own pig farming and is still importing from other regions. Meanwhile, in North Satar Mese, Langke Rembong, Ruteng, Lelak, North Rahong, West Cibal and Reok sub-districts which received LQ>1 results which means that the pig farming sector is able to meet the needs of its own region and can also be exported to other regions. The results of this study can be used as a reference for the preparation of the Regional Spatial Plan (RSP) of Manggarai Regency.